Impact of essential-oil-based cleaning products on indoor air quality: From liquid composition to test emission chamber. Issue 4 (September 2019) - Angulo Milhem, S.; Verriele, M.; Nicolas, M.; Thevenet, F.
Abstract: As society has become aware of health hazards related to the exposure to chemicals, major efforts have been made to address indoor air current problematic. Consequently, popularity of "green" cleaning products has upsurge. These products are formulated with essential-oils relying on their anti-bacterial properties to improve indoor air quality. Indeed, essential oils might contain a hundred of odorous molecules, mainly terpenes and terpenoids (TerVOCs) which acts as antibacterial agents. Nonetheless, do essential-oil-based products really contribute to indoor air quality improvement? This study is addressed to evaluate emissions from the use of essential-oils-based cleaning products by various scale experiments. Firstly, a correlation of liquid composition from 7 natural cleaning products with their emission potentials has been investigated. Volatile fractions are evaluated by using micro-chamber testing. A total of 28 terpenes are quantified among products in the liquid form. Nevertheless, only 22 species are detected in gas samples with a yield ranking from 9.1 % to 99.8 %. Results do not verified a direct correlation between liquid mass and emitted concentrations of terpenes. Indeed, chemical affinities between terpenes and solvent matrix in product formulation are evidenced. Then, 4 products from different cleaning purposes have been selected for emission evaluation in a test chamber of 1-m3. Product application process are correlated to real case scenario regarding applied quantity and loading factor. Emitted terpenes and carbonyl compounds are quantified by off-line and on-line chromatography measurements. Results evidenced that peak concentrations from terpenes reached up to 1.5 h after cleaning activity. Major compound emitted concentration range from 121 to 152 μg/m3, in the test chamber, for different product categories. Specific emission dynamic is evidenced for formaldehyde, in where continuous increasing concentration is revealed due to the presence of formaldehyde releasers. This study contributes to further assessment of exposure hazards related to cleaning activities.